LUDWIG’S ANGINA: EARLY DIAGNOSIS AND AIRWAY MANAGEMENT IN DEEP CERVICAL INFECTIONS - Ferreira Filho, José Laurentino; Bella, Ana Paula Granja Scarabel Nogueira; Caramez, Renata Helena Ferreira; Farias, Aline; Cunha, Vivian Rabelo; Ferreira, Carolina Dieguez Rabelo; Nascimento, Larissa Priscilla dos Santos; Costa Neto, Wilton; Azevedo, Claudiony Henrique Dantas de Sousa; Veloso, Cristiano; Dias, Marcelo Magalhães; de Sousa, Gabrielle Oliveira; et al. (Seven Editora, 2026)
Ludwig’s angina is a rapidly progressive deep cervical infection characterized by bilateral involvement of the submandibular, sublingual, and submental spaces, frequently associated with odontogenic infections. It is considered a potentially fatal medical emergency due to the high risk of acute airway obstruction, mediastinal spread, and sepsis. This study aimed to critically analyze the scientific evidence regarding early diagnosis and airway management in Ludwig’s angina, emphasizing the main prognostic factors, therapeutic strategies, and anesthetic-surgical approaches currently employed. This is an integrative literature review conducted according to the methodological assumptions proposed by Whittemore and Knafl. The bibliographic search was performed in the PubMed/MEDLINE, Scopus, Web of Science, and SciELO databases using descriptors related to Ludwig’s angina, deep neck infections, airway management, and odontogenic emergencies. Articles published within the last ten years, available in full text, and directly related to the proposed topic were included. The findings demonstrated that early recognition of clinical signs of respiratory compromise, combined with cervical computed tomography evaluation and the immediate initiation of broad-spectrum antibiotic therapy, is essential for reducing complications and mortality. Furthermore, airway management remains the main therapeutic challenge, especially in the presence of anatomical distortion caused by diffuse cervical edema, trismus, and elevation of the oral floor. Techniques such as awake fiberoptic intubation and early tracheostomy were identified as safer strategies in advanced cases. It is concluded that Ludwig’s angina remains a highly severe clinical condition requiring a multidisciplinary approach, rapid diagnosis, and early airway intervention to optimize prognosis and prevent fatal outcomes.